ETNOGRAFI VIRTUAL PERILAKU IMPULSIVE BUYING DI MEDIA SOSIAL (STUDI PADA AKUN AUTOBASE @DISCOUNTFESS) - Wijaya, Chikal Clarasati; Arifah, Paujiatul; Ardhiani, Ocvita (Universitas Gunadarma, 2024)
The purpose of this study is to describe how the pattern of impulsive buying behavior found in the X Autobase @discountfess account. Social media, one of which functions as a promotional media, can then form a consumptive culture in its users. The impulsive buying stage can occur in a person because of the offers that continue to hit them. The behavior pattern was analyzed using virtual ethnography with the Analysis of Cyber Media (AMS) method as a guide. The results show that interaction and support from online communities, especially through comments and interactions between users, can increase subjective norms related to consumptive patterns. The bigger and more attractive the discount offered, the more interaction occurs and vice versa.